2017
DOI: 10.1002/gps.4827
|View full text |Cite
|
Sign up to set email alerts
|

The association amongst visual, hearing, and dual sensory loss with depression and anxiety over 6 years: The Tromsø Study

Abstract: Dual sensory loss resulted in increased depression symptomatology over time and posed an additional long-term risk to depression severity beyond having a single sensory loss only. Only hearing loss is associated with anxiety symptoms. Older adults with vision, hearing, and dual sensory loss have different mental health profiles. Therefore, management and intervention should be tailored to the type of sensory loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
93
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 54 publications
9
93
3
3
Order By: Relevance
“…Furthermore, our results contribute to the small and contradictory evidence regarding the longitudinal association between HL and depression. Previous longitudinal studies examining severity of depression symptoms have found no association between HL and depression, whereas difference in depression symptoms pre‐HL and post‐HL onset has been observed . Our findings highlight a significant longitudinal association between HL with the presence of depression symptoms.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Furthermore, our results contribute to the small and contradictory evidence regarding the longitudinal association between HL and depression. Previous longitudinal studies examining severity of depression symptoms have found no association between HL and depression, whereas difference in depression symptoms pre‐HL and post‐HL onset has been observed . Our findings highlight a significant longitudinal association between HL with the presence of depression symptoms.…”
Section: Discussioncontrasting
confidence: 45%
“…Communication difficulties observed in HL may underlie the association with depression, especially through increased social isolation and loneliness, with perceived lack of social support associated with depression onset . Furthermore, reductions in help‐seeking and increases in comorbid anxiety might also contribute to the depression and HL relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In apparent contrast to results from previous cross-sectional (10,76) and longitudinal studies (60,77), an association between vision loss and anxiety was not found. A recent longitudinal cohort study in older adults (n=7584) by Frank et al also found no association between self-reported visual impairment and anxiety (64).…”
Section: Discussioncontrasting
confidence: 99%